Magnetic Resonance Imaging in 50 Captive Non-domestic Felids - Technique and Imaging Diagnoses - Hecht, Silke; Cushing, Andrew C.; Williams-Hagler, Dottie A.; Craig, Linden E.; Thomas, William B.; Anderson, Kimberly M.; Ramsay, Edward C.; Conklin, Gordon A. (Frontiers in Veterinary Science, 2022)
Magnetic resonance imaging (MRI) is the recognized gold standard for diagnostic imaging of the central nervous system in human and veterinary patients. Information on the use of this modality and possible imaging abnormalities in captive non-domestic felids is currently limited to individual case reports or small case series. This retrospective study provides information on technique and imaging findings in a cohort of cases undergoing MRI at an academic Veterinary Medical Center. The University of Tennessee College of Veterinary Medicine MRI database was searched for non-domestic felids undergoing MRI of the brain or spine from 2008 to 2021. Medical record data were recorded, and MRI studies were reviewed. Fifty animals met the inclusion criteria. The most common brain diseases were Chiari-like malformation (n = 8) and inflammatory conditions (n = 8). Other abnormalities included pituitary lesions (n = 5), brain atrophy (n = 2), and one each of metabolic and traumatic conditions. Fourteen animals had a normal brain MRI study. The most common spinal abnormality was intervertebral disc disease (n = 7). Other disorders included vertebral dysplasia (n = 2), presumptive ischemic myelopathy (n = 1), subdural ossification causing spinal cord compression (n = 1), and multiple myeloma (n = 1). Spinal cord swelling of undetermined cause was suspected in two animals, and seven patients had a normal MRI study of the spine. MRI is a valuable tool in the diagnostic workup of non-domestic felids with presumptive neurologic disease.